2018
DOI: 10.1111/cts.12600
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drug–Drug Interactions of Rucaparib and CYP1A2, CYP2C9, CYP2C19, CYP3A, and P‐gp Substrates in Patients With an Advanced Solid Tumor

Abstract: This phase I study (CO‐338‐044; NCT02740712), conducted in patients with advanced solid tumors, evaluated the effect of the poly(ADP‐ribose) polymerase (PARP) inhibitor rucaparib on the pharmacokinetics (PK) of caffeine 200 mg, warfarin 10 mg, omeprazole 40 mg, and midazolam 2 mg (cytochrome P450 (CYP) 1A2, CYP2C9, CYP2C19, and CYP3A substrates; dosed as a cocktail) and digoxin 0.25 mg (P‐glycoprotein (P‐gp) substrate; dosed separately) without rucaparib and following oral rucaparib 600 mg b.i.d. Geometric mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 26 publications
3
32
0
Order By: Relevance
“…Seville oranges and grapefruit should be avoided in those patients taking olaparib, since they are CYP3A inhibitors, 12 while rucaparib may increase the effects of caffeine. 17 PARP Inhibitor as Single Agent: Maintenance and Treatment Monotherapy First-line maintenance randomized trials have shown a robust disease-free survival/progression-free survival improvement with PARPi treatment in ovarian cancer; overall survival data remain immature to date. [18][19][20] Two placebo-controlled phase III trials have assessed switch-maintenance PARPi treatment in patients that respond to front-line platinum; SOLO1 (NCT01844986) assessed olaparib in patients with ovarian cancer harboring somatic and germline BRCAm, 18 and PRIMA/ENGOT-Ov26 (NCT02655016) assessed niraparib in the overall population (non-restricted to BRCAm carriers).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Seville oranges and grapefruit should be avoided in those patients taking olaparib, since they are CYP3A inhibitors, 12 while rucaparib may increase the effects of caffeine. 17 PARP Inhibitor as Single Agent: Maintenance and Treatment Monotherapy First-line maintenance randomized trials have shown a robust disease-free survival/progression-free survival improvement with PARPi treatment in ovarian cancer; overall survival data remain immature to date. [18][19][20] Two placebo-controlled phase III trials have assessed switch-maintenance PARPi treatment in patients that respond to front-line platinum; SOLO1 (NCT01844986) assessed olaparib in patients with ovarian cancer harboring somatic and germline BRCAm, 18 and PRIMA/ENGOT-Ov26 (NCT02655016) assessed niraparib in the overall population (non-restricted to BRCAm carriers).…”
Section: Reviewmentioning
confidence: 99%
“…Treatment with rucaparib may increase the effect of omeprazole. 17 Dysgeusia has been reported in ~10%-40% of patients, more commonly with rucaparib ( Table 3). Ensuring that patients maintain adequate oral hygiene care may also be helpful for dysgeusia management.…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Midazolam is a short-acting benzodiazepine (used for sedation [11]) and is metabolized by CYP3A4 in the liver to 1′-hydroxy-midazolam (1′-OH midazolam) [12,13]. Midazolam has been validated as a probe in other studies investigating CYP3A4 activity [14][15][16][17].…”
Section: Pharmacokinetics and Safety Assessmentsmentioning
confidence: 99%
“…Breastfeeding is contraindicated during treatment with rucaparib . Coadministration of rucaparib can increase systemic exposure of cytochrome P450 (CYP) 1A2, CYP3A, CYP2C9, or CYP2C19 substrates . If clinically indicated, dose adjustments may be considered for substrates of CYP1A2, CYP3A, and CYP2C9, particularly those with a narrow therapeutic index (e.g., tizanidine, cyclosporine, and warfarin, respectively).…”
Section: Management Of Rucaparib Toxicitymentioning
confidence: 99%